2006
DOI: 10.1007/s10750-006-0104-5
|View full text |Cite
|
Sign up to set email alerts
|

Inter-genotype variation in reproductive response to crowding among Daphnia pulex

Abstract: Crowding is known to have a major influence on reproduction in the freshwater microcrustacean Daphnia pulex. We analyzed reproductive output of six different D. pulex genotypes under two different density regimes in the laboratory. Four of these genotypes reproduce via obligate parthenogenesis, allowing thorough analysis of the life history strategies of some asexual lines. Among 30,109 neonate offspring and 1041 resting egg ephippia collected, several trends were evident. Crowding induced increased resting eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 101 publications
(143 reference statements)
1
26
0
Order By: Relevance
“…Further, low maternal food availability is shown to decrease the likelihood that progeny will develop as dauer larvae (Figure 3). These observed effects of maternal conditions on progeny life history in C. elegans could represent a switch to the production of fewer, better provisioned eggs, in poor conditions and would mirror observations in Daphnia [6][10]. As such they would represent attempts to match progeny development to the expected environmental conditions and are therefore likely to be adaptive [1], [4].…”
Section: Discussionmentioning
confidence: 99%
“…Further, low maternal food availability is shown to decrease the likelihood that progeny will develop as dauer larvae (Figure 3). These observed effects of maternal conditions on progeny life history in C. elegans could represent a switch to the production of fewer, better provisioned eggs, in poor conditions and would mirror observations in Daphnia [6][10]. As such they would represent attempts to match progeny development to the expected environmental conditions and are therefore likely to be adaptive [1], [4].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the literature, crowding by conspecifics reduces adult growth and egg production rates in Daphnia pulex (Nishikawa and Ban, 1998) and Simocephalus vetulus (Lee and Ban, 1999), clutch size in Daphnia pulex (Fitzsimmons and Innes, 2006), Daphnia hyalina (Seitz, 1984), Daphnia carinata (Matveev, 1993) and Daphnia magna (Guisande, 1993) given excess food. What causes such negative effects on demographic parameters?…”
Section: Discussionmentioning
confidence: 87%
“…The evidence indicates that a reduction in feeding due to crowding does not necessarily cause a diminution of clutch size in older animals. Since inter-genotype variation in reproductive responses to crowding has been shown in Daphnia pulex (Fitzsimmons and Innes, 2006), smaller clutch sizes at older age under crowded conditions may be a reproductive feature of the clone used in this study, but is not attributable to food shortage. If the reproductive responses to crowded conditions adapt to forthcoming severe food conditions as described above, the reduction in offspring numbers may also be adaptive.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The frequency of resting egg production was found to be lower in Daphnia populations that persist with high numbers all through the year than in those that disappear from the water column during some seasons Tessier, 2004a, 2004b). Furthermore, recent studies have shown intra-specific variation in sexual reproduction in response to given conditions (Tessier and Cáceres, 2004;Fitzsimmons and Innes, 2006). If harsh seasons were to disappear due to environmental changes that enable Daphnia to persist through the year in the water column, then genetic strains that are sensitive to environmental stimuli for triggering sexual reproduction may be outcompeted by less sensitive lines because of decreased individual fitness, at least with respect to resting egg production.…”
Section: Introductionmentioning
confidence: 99%